THE DESIGN OF THE CONSTRUCTION OF RETAINING WALLS ON THE RIVER SLOPES OF KUIN - Achmad Yasrifullah; Adriani Adriani (CERUCUK, 2020)
North Kuin Street, North Kuin, North Banjarmasin Subdistrict, South Kalimantan Sub-district is right on the outskirts of Kuin River. Precisely the road that is in front of the Sultan Suriansyah Mosque, where the road has experienced cracks that can potentially occur landslides. In the event of an avalanche, it will result in obstructed traffic activities on the road which also affect the economy of the surrounding community. So from that the soil retaining wall is needed to maintain the stability of the land on the outskirts of the Kuin River so that landslides do not occur.This design begins with identifying problems that occur.  Next is data collection of investigations in the field and laboratory. Then the data obtained are analyzed and interpreted and then visualized in the form of stratigraphy by plotting the type of soil by the results of sondir and boring that have been interpreted. After that, check the initial condition of the slope so that the shape of the avalanche can be identified. Then proceed with calculating the forces acting on the retaining wall due to traffic loads and other loads above it to obtain carrying capacity from the ground. Then proceed with modeling and analysis using Geo Studio 2012 software to see the value of SF (safety factor). At the end of the calculation the volume and price of the work unit are calculated to obtain the amount of the budget plan (RAB).       From the results of the analysis of the design of anchor plaster, it was obtained a box profile of FSP VIL steel plaster with a total length of 28 m plaster. At stake uses a steel pipe with a diameter of 91.44 cm which is set at a depth of 28 m. For slope stability with pile reinforcement obtained SF = 1.835> 1.5, it can be said to be safe. Based on the calculation of the volume and price of the work unit, this design requires a cost of Rp. 7,340,166,486, -